Dukungan Spiritual dan Praktik Agama bagi Kualitas Hidup Pasien Kanker - Sepang, Gledis Merry; Waluyo, Agung; Nuraini, Tuti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to study and review each research article and summarize the relationship between spirituality and religious practices on the quality of life of cancer patients. The method used is a literature review through databases such as Scopus, PubMed, EBSCOHost, Science Direct, Clinicalkey Nursing, ProQuest, and Jstor (Springer). The research results showed that there were 10 articles that were relevant to the objectives, where spirituality/religiosity had a positive relationship with physical, emotional and social functioning. On the other hand, it is negatively associated with symptoms of disease, such as pain or emotional and physical exhaustion. In conclusion, spiritual aspects and religious practices are positively correlated with the quality of life of cancer patients. Keywords: Quality of Life, Cancer Patients, Spiritual-Religious Practices